2004
DOI: 10.1074/jbc.m407073200
|View full text |Cite
|
Sign up to set email alerts
|

Two Regions Promote U11 Small Nuclear Ribonucleoprotein Particle Binding to a Retroviral Splicing Inhibitor Element (Negative Regulator of Splicing)

Abstract: The Rous sarcoma virus (RSV) negative regulator of splicing (NRS) is an RNA element that represses splicing and promotes polyadenylation of viral RNA. The NRS acts as a pseudo 5 splice site (ss), and serine-arginine (SR) proteins, U1snRNP, and U6 small nuclear ribonucleoproteins (snRNPs) are implicated in its function. The NRS also efficiently binds U11 snRNP of the U12-dependent splicing pathway, which is interesting, because U11 binds only poorly to authentic substrates that lack a U12-type 3 splice site. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…It was recently shown that a G-rich sequence downstream of the U11 consensus site is required for optimal U11 binding to the NRS in vitro and in vivo (30). Here, we show that the G-rich element specifically interacts with hnRNP H, a member of the heterogeneous nuclear ribonucleoprotein (hnRNP) family of RNA-binding proteins (37).…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…It was recently shown that a G-rich sequence downstream of the U11 consensus site is required for optimal U11 binding to the NRS in vitro and in vivo (30). Here, we show that the G-rich element specifically interacts with hnRNP H, a member of the heterogeneous nuclear ribonucleoprotein (hnRNP) family of RNA-binding proteins (37).…”
mentioning
confidence: 82%
“…For snRNP co-precipitation, Protein A-Sepharose beads were incubated with buffer, preimmune serum, or hnRNP H antibodies, and 10 l of beads were added to 50 l of nuclear extract under splicing conditions for 1 h. Samples were washed as above, treated with Proteinase K to release nucleic acids, and then phenol-extracted and subjected to Northern blotting with U1 and U11 riboprobes as described (30).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations